Angina and left ventricular dysfunction: can we 'reduce' it?. (10th April 2019) - Biscaglia, Simone; Tebaldi, Matteo; Mele, Donato; Balla, Cristina; Ferrari, Roberto
Abstract: Despite the evolution in pharmacology and devices, recurrent and persistent angina still represent a frequent issue in clinical practice. A 69-year-old Caucasian female patient has history of surgical aortic valve replacement with a bioprosthesis for severe aortic stenosis with subsequent transcatheter valve-in-valve implantation for bioprosthesis degeneration and single coronary artery bypass graft with left internal mammary artery on left anterior descending (LAD). After transcatheter aortic valve implantation, she started to complain angina [Canadian Cardiovascular Society (CCS) Class III], effectively treated with bisoprolol uptitration and ivabradine 5 b.i.d. addition. After 6 months, she had a non-ST segment elevated myocardial infarction with evidence of left main occlusion and good functioning aortic bioprosthesis. A retrograde drug-eluting balloon percutaneous coronary intervention (PCI) on LAD (in-stent restenosis) was performed. However, the patient continued to complain angina (CCS Class II–III), even after further ivabradine increase to 7.5 mg b.i.d. After 4 months, the patient underwent Reducer implantation. After 2 months, angina started to improve and the patient is currently angina free. In the last decades, PCI materials and stents greatly improved. Medical therapy (such as β-blockers) has been shown not only to improve symptoms but also to add a prognostic benefit in patients with reduced ejection fraction (EF). Ivabradine showed additional benefits in patients with angina and reduced EF. However, still a relevant portion of patients complain refractory angina. The COSIRA trial showed that a coronary sinus Reducer was associated with greater angina relief than the sham procedure and could be a further step in angina treatment.